Geochemical properties of surface sediments in the inner Gulf of Thailand - Bingbing Wei (PANGAEA, 2025)
This dataset compiles published geochemical properties of surface sediments in the inner Gulf of Thailand, including sediment composition (clay, silt and sand), median grain size, fine fraction proportion, total organic carbon content (TOC), TOC/total nitrogen (TN) ratio, δ13C of bulk OC, as well as the abundances of total, high-molecular-weight (HMW) and low molecular-weight (LMW) alkanes. These data are sourced from Bai et al. (2021) and Lin et al. (2023). Using the published TOC/TN ratio and δ13C of bulk OC, we estimated the contributions of marine, river, and coastal organic carbon sources through a Bayesian Markov chain Monte Carlo (MCMC) model.